Spectral Sensitivity of the Planarian Ocellus - Brown, H. Mack (The Rockefeller University Press, 1968)
The ocellar potential (OP) of planaria was recorded using microelectrode techniques. The action spectrum and spectral sensitivity of the OP are described. Maximum OP sensitivity was found with 508 nm light. A moderate increase in sensitivity to blue light was observed. This is typical of many invertebrate photoreceptors and was shown, by selective chromatic adaptation, not to indicate the presence of a second pigment.